SPATIAL SENSE ABILITY INSTRUMENT FOR PRIMARY SCHOOL STUDENTS - Putri, Hafiziani Eka; Nuraeni, Fitri; Haftani, Dwi Anisa; Rosalia, Elvira; Pratama, Nouval (Metodik Didaktik, 2022)
This research is motivated by the importance of spatial sense skills possessed by elementary school students. The research aims to develop an instrument of spatial sense ability suitable for elementary school students. The indicators developed in the preparation of questions include: 1) classifying real objects into 3D form (building space); 2) investigating, exploring, and describing geometry in nature and the real world; 3) exploring the directional relationship of objects in space; 4) analyzing the nature of 3D shapes and interpreting 3D shapes into 2D forms. Research and Development was chosen as the method of this research. A total of 33 grade VI students of SDN 1 Nagri Kidul, Purwakarta Regency, West Java Province, were the samples in this study. The sample was selected by purposive sampling. The instrument used is an essay test consisting of seven questions regarding the geometry of cubes and blocks. The expert (Professor in the field of mathematics education) validated the seven questions that had been prepared. Expert considerations are used as the basis for the improvement of the compiled questions. Then the questions that have been corrected are tested on the research sample. The results of the trial were calculated for validity, reliability, difficulty index, and discriminatory power. Of the seven questions compiled, six were declared valid, reliable, and had high discriminatory power, and the level of difficulty of the questions consisted of medium and difficult. Thus, 6 of the seven items developed can be used by teachers or researchers as an instrument to measure the spatial sense abilities of elementary school students, primarily fifth-grade students.